Distribution and release of phosphorus fractions associated with soil aggregate structure in restored wetlands. (May 2019) - Cui, Hu; Ou, Yang; Wang, Lixia; Wu, Haitao; Yan, Baixing; Li, Yingxin
Abstract: Phosphorus, a dominating element responsible for eutrophication, is a potential limiting nutrient in wetland ecosystem. In this study, the release risk of phosphorus was evaluated by investigating the distribution of phosphorus fractions in different grain-sizes of soil aggregates in wetlands with restoration durations of 1, 2, 3, 5, 13 or 19 years. The results showed that the soil aggregate structure tended to be stable when paddy fields were changed into wetland, though aggregate structure first condensed fine-aggregates (<0.25 mm) into coarse-aggregates (>0.25 mm), which was then reversed until the process stabilized after 5 restoration years. With the exception of labile inorganic phosphorus (L-Pi), which continuously decreased within extended abandoned period, total phosphorus (TP), labile organic phosphorus (L-Po), moderately labile organic phosphorus (Ml-Po), iron-aluminum bound phosphorus (Fe·Al-P), calcium-magnesium bound phosphorus (Ca·Mg-P), humic phosphorus (Hu-P) and residual phosphorus (Re-P) concentrations presented a unimodal tendency with a peak at the 2nd or 3rd restoration year, respectively. TP, L-Pi, L-Po and Re-P tended to decrease with decreasing soil aggregate grain-size, and Ml-Po was enriched in small macro-aggregates (0.25–1 mm) and micro-aggregates (0.053–0.25 mm). Macro-aggregates carried Fe·Al-P and Ca·Mg-P. Adsorption isotherm simulation results demonstrated that the retention capacity for phosphorus of a restored wetland first increased and then decreased with extended abandonment period, and macro-aggregates showed a considerable capacity to retain phosphorus. Fe.Al-P and Hu-P had potential release risk with approximate amounts of 197.25–337.25 mg kg −1 and 131.28–185.72 mg kg −1, in associated with anaerobic environment and aggregate structure. Highlights: Wetland restoration increase the proportion of coarse-aggregates. TN, SOM, Fe and Mn tended to condense in coarse-aggregates. Macro-aggregates were the carriers of Fe·Al-P and Ca·Mg-P. Macro-aggregates had considerable capacity to retain phosphorus. The release risk of Fe·Al-P and Hu-P in July–August needs to be focused.